2015
DOI: 10.1038/ejhg.2015.117
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for genetic testing for colorectal cancer within a population-based screening program: a discrete choice experiment

Abstract: This study explored individuals' preferences for genetic testing for colorectal cancer (CRC) in a screening situation and their willingness to participate in genetic testing for Lynch syndrome, familial adenomatous polyposis (FAP), and familial colorectal cancer (FCC). For that purpose, 532 respondents aged 55-65 years completed a Discrete Choice Experiment. Using panel latent class models, the preferences for two screening situation characteristics (the probability of being genetically predisposed and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Limited evidence exists on preferences for genetic testing to identify Mendelian CRC risk and our study is the first to explore patients’ preferences for MPS genetic testing. Efforts to date have focused on the general population perspective in the context of population-based screening programs, with researchers concluding that the public is willing to undergo screening, but that choices vary depending on prior experience with genetic testing and anxiety about being genetically predispos1ed to developing CRC [ 18 ]. These results align with our findings indicating that while, on average, patients value information on genetic causes of CRC, significant heterogeneity is present in the sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited evidence exists on preferences for genetic testing to identify Mendelian CRC risk and our study is the first to explore patients’ preferences for MPS genetic testing. Efforts to date have focused on the general population perspective in the context of population-based screening programs, with researchers concluding that the public is willing to undergo screening, but that choices vary depending on prior experience with genetic testing and anxiety about being genetically predispos1ed to developing CRC [ 18 ]. These results align with our findings indicating that while, on average, patients value information on genetic causes of CRC, significant heterogeneity is present in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…This utility may be partially offset by direct and indirect costs of genetic testing, including adverse impacts of testing. Past studies eliciting preferences for genetic testing in the context of CRC focused on the general population, who consider personal utility and trade-offs differently from patients when valuing testing [ 4 , 18 ]. Patients’ personal utility for information on genetic causes of CRC and preferences for MPS testing of Mendelian CRC risk are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to many important ethical and legal hurdles, attainment of genetic information requires a willingness of the population to participate. Although there is a strong public support for genetic testing for health purposes (for instance 89.1% of participants in a Dutch online panel survey of 55-59-year-olds reported they would take part in genetic screening for colorectal cancer 19 ), it is unknown how the offer of genetic testing for screening purposes may affect participation. Assuming eligibility under a genetics-based program would revert to being judged based on age risk for those who refuse to participate in genetic testing, a proportion of those eligible based on their genetic risk for age would, in reality, not be screened, and a proportion of those ineligible based on their genetic risk for age would, in reality, be screened.…”
Section: Project Limitationsmentioning
confidence: 99%
“…Risk stratification and personalised surveillance could substantially increase the detection rate and earlier detection for cancers in younger individuals (especially for those under 50 years of age and therefore not eligible for the NBCSP), reduce the number of investigations for false‐positive results, reduce the harm due to overuse of diagnostic or invasive treatments so that resources can be allocated to those who would benefit most from more regular surveillance 13 . Furthermore, it has been suggested that personalised risk stratification could improve compliance with population CRC screening strategies 16 …”
Section: Risk Stratificationmentioning
confidence: 99%